Pergeseran Nilai dan Peran Lembaga Keagamaan dalam Penanggulangan KDRT [Studi Lembaga Keagamaan di Kota Yogyakarta] - Amilia, Fatma; Mansur, Mansur; Saifuddin, Saifuddin (UIN Sunan Kalijaga, 2016)
Religious institutions looked having an important role in responding a violence, especially for women at domestic violence. It is because our understanding that any religion has never agreed and received any kind of violence. However, time has changed, campaign and gender mainstreaming has been actively issued by the government and non government organizations. Therefore, the interpretation of the devine text by the religious leaders has also shifted. This article elaborates the role and paradigm shift in the religious institutions in anticipating and rehabiliting domestic violence in Yogyakarta.